Association between Inflammatory Factors, Vitamin D, Long Non‐Coding RNAs, MALAT1, and Adiponectin Antisense in Individuals with Metabolic Syndrome. Issue 5 (26th January 2023) - Rashidmayvan, Mohammad; Khorasanchi, Zahra; Nattagh‐Eshtivani, Elyas; Esfehani, Ali Jafarzadeh; Sahebi, Reza; Sharifan, Payam; Assadiyan‐sohan, Parisa; Aghasizadeh, Malihe; Avan, Amir; Ghayour‐Mobarhan, Majid; Ferns, Gordon
Abstract : Background: Metabolic syndrome (MetS) is a common clustering of cardiovascular risk factors associated with increased inflammation. Long non‐coding RNA (LncRNA) are involved in many of the body's metabolic activities, including inflammation. Vitamin D may play a vital role in preventing metabolic syndrome risk factors. This study aimed to evaluate the status of inflammation and expression of LncRNA and their relationship with serum vitamin D levels in patients with metabolic syndrome. Method: This cross‐sectional study included staff and Mashhad University of Medical Sciences students between 30 and 50 years old who met the International Diabetes Federation criteria for Mets. Total RNA was extracted from both frozen clinical samples using the Trizol reagent. Results: A total of eighty people were recruited into the two groups, with and without MetS. Inflammatory markers were higher in the individuals in the MetS group, and linear regression showed an inverse association between serum vitamin D and LncRNAs. There was a positive association between inflammatory biomarkers, lipid profiles and Adiponectin Antisense (APQ AS) expression. Conclusion: APQ AS and MALAT1 levels are positively associated with inflammatory biomarkers and inverse relation between MALAT1 and serum 25 (OH) D concentration. Abstract : This figure illustrates that MALAT1 can be linked to increased cytokine production and inflammation by increasing the inflammatory factors TNF‐A and IL‐6 and increasing the severity of the metabolic syndrome.